A microchondrule‐bearing micrometeorite and comparison with microchondrules in CM chondrites. (27th March 2019) - Suttle, M. D.; Genge, M. J.; Salge, T.; Lee, M. R.; Folco, L.; Góral, T.; Russell, S. S.; Lindgren, P.
Abstract: We report the discovery of a partially altered microchondrule within a fine‐grained micrometeorite. This object is circular, <10 μm in diameter, and has a cryptocrystalline texture, internal zonation, and a thin S‐bearing rim. These features imply a period of post‐accretion parent body aqueous alteration, in which the former glassy igneous texture was subject to hydration and phyllosilicate formation as well as leaching of fluid‐mobile elements. We compare this microchondrule to three microchondrules found in two CM chondrites: Elephant Moraine (EET) 96029 and Murchison. In all instances, their formation appears closely linked to the late stages of chondrule formation, chondrule recycling, and fine‐grained rim accretion. Likewise, they share cryptocrystalline textures and evidence of mild aqueous alteration and thus similar histories. We also investigate the host micrometeorite's petrology, which includes an unusually Cr‐rich mineralogy, containing both Mn‐chromite spinel and low‐Fe‐Cr‐rich (LICE) anhydrous silicates. Because these two refractory phases cannot form together in a single geochemical reservoir under equilibrium condensation, this micrometeorite's accretionary history requires a complex timeline with formation via nonequilibrium batch crystallization or accumulation of materials from large radial distances. In contrast, the bulk composition of this micrometeorite and its internal textures are consistent with a hydrated carbonaceous chondrite source. This micrometeorite is interpreted as a fragment of fine‐grained rim material that once surrounded a larger parent chondrule and was derived from a primitive carbonaceous parent body; either a CM chondrite or Jupiter family comet.